PENGARUH FAKTOR INDEPENDENSI, PENGALAMAN, TEKANAN ANGGARAN WAKTU DAN BIAYA AUDIT TERHADAP KUALITAS AUDIT - Devia Evrillia W; Jesyca Viani Ketty; Vince De Venelli (KRISNA: Kumpulan Riset Akuntansi, 2022)
The study entitled "the effect of Independent Factor, Experience, Time Budget Pressure, and Audit Fee to Audit Quality". This study aims to determine the effect of Independent Factor, Experience, Time Budget Pressure and Audit Fee to Audit Quality. Because, even though the auditor is smart, if the auditor does not have integrity and a professional attitude, then the results of audit quality will definitely be a big question for users of the financial statements.Researchers have collected 20 articles with research year : 2021, researchers will discuss several important aspects of research, like research mehods, theories used and research models. The Articles are national articles obtained from several provinces in Indonesia. The articles we get are national articles obtained from several provinces in Indonesia. For research results, we define the scope, and sector studied. This study provides an understanding of the importance of the auditor`s character on audit quality in a company.